Management of irrigation systems: From government to water user associations - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Approximately 40 percent of the world's food and 60 percent of its grain are produced under irrigation. Between 1900 and 1950, the total area under irrigation worldwide nearly doubled, from 48 million hectares to 94 million hectares. By 2000, it had reached 240 million hectares. The expansion entailed expensive infrastructure and strained governments' capacity to afford and manage these systems.